Treatment of Recurrent Basilar Artery Aneurysms at Fenestration After Coils using Flow Diverter Combined with Coils: Case Report (London Journal of Medical and Health Research, 2024)
An aneurysm at the fenestration position of the basilar artery is an extremely rare condition that presents challenges in treatment. Aneurysm recurrence is a complication that can occur after interventions for aneurysms in this location. We report the case of a 43-year-old male patient with a ruptured basilar artery aneurysm treated with coils. After 30 months of follow-up, the aneurysm recurred and was treated with a flow diverter stent combined with coils.
Keywords: relative length of telomeric repeats; coronary heart disease with myocardial infarction; percentage of the calibrator; oxidative stress; protective effect; chromosomes.; Human bite; soft tissue necrosis